2011
DOI: 10.1103/physreva.84.043430
|View full text |Cite
|
Sign up to set email alerts
|

Coherent manipulation of spin-wave vector for polarization of photons in an atomic ensemble

Abstract: We experimentally demonstrate the manipulation of two-orthogonal components of a spin wave in an atomic ensemble. Based on Raman two-photon transition and Larmor spin precession induced by magnetic field pulses, the coherent rotations between the two components of the spin wave is controllably achieved.Successively, the two manipulated spin-wave components are mapped into two orthogonal polarized optical emissions, respectively. By measuring Ramsey fringes of the retrieved optical signals, the π/2-pulse fideli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
(21 reference statements)
1
10
0
Order By: Relevance
“…In efforts to resolve the mystery of the superconducting mechanism, plenty of experiments have been carried out on the impurity effects in iron-based superconductors. Ways to introduce scattering centers include chemical substitutions [21][22][23][24][25][26][27][28][29][30][31][32][33] and particle irradiations [34][35][36][37][38]. Unfortunately, the conclusions remain highly controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In efforts to resolve the mystery of the superconducting mechanism, plenty of experiments have been carried out on the impurity effects in iron-based superconductors. Ways to introduce scattering centers include chemical substitutions [21][22][23][24][25][26][27][28][29][30][31][32][33] and particle irradiations [34][35][36][37][38]. Unfortunately, the conclusions remain highly controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on Mn impurities showed that T c was strongly suppressed in Ba 0.5 K 0.5 Fe 2 As 2 [21,23] and Ba(Fe −y 1 Co y ) 2 As 2 systems [24], while T c is not suppressed or is even enhanced in Mn-doped FeSe 0.5 Te 0.5 superconductors [26]. Zn impurity suppresses T c rapidly in BaFe − x 1.89 2 Zn x 2 Co 0.11 As 2 [25], whereas the superconducting state is retained robustly in Fe −y 1 Zn y Se 0.3 Te 0.7 [27]. Theoretically it is proposed that the pairing symmetry in iron-based superconductors can differ from material to material [7].…”
Section: Introductionmentioning
confidence: 99%
“…The measured optical depth of the cold atoms is about 1.5 and the trap temperature can reach ~200 µK (see [12] for the experimental details).…”
Section: Coherent Manipulation Of Spin Wave Vector For Polarization Omentioning
confidence: 99%
“…In 2011, we demonstrated an experiment on the two unitary rotations R(,) and R z ( z ) on the basis of their formation by two orthogonal spin waves in an atomic ensemble [12]. The relevant 87 Rb levels involved in the storage, Raman manipulation and readout processes are shown in Figure 11 …”
Section: Coherent Manipulation Of Spin Wave Vector For Polarization Omentioning
confidence: 99%
See 1 more Smart Citation